2008
DOI: 10.1002/jcc.21131
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of two functional groups through the benzene ring: Theory and experiment

Abstract: Energies of 132 benzene para bis-derivatives calculated within the framework of the density functional theory at the level B3LYP/6-311+G(d,p)//B3LYP/6-311+G(d,p) were used for correlations of two types. Correlation with the experimental enthalpies of formation clearly revealed that the published experimental data are generally not dependable and may be loaded with errors of more than 10 kJ mol(-1). On the other hand, the calculated relative energies are biased so that the interaction of the two substituents is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Further calculations demonstrated that the Hammett relationship of bond dissociation energies is determined only by the change of electron demand during the homolysis process. This study provided an interesting new answer to the longstanding problem of how to understand and predict the Hammett relationship in the bond homolysis processes [20][21][22]. …”
Section: Discussionmentioning
confidence: 96%
“…Further calculations demonstrated that the Hammett relationship of bond dissociation energies is determined only by the change of electron demand during the homolysis process. This study provided an interesting new answer to the longstanding problem of how to understand and predict the Hammett relationship in the bond homolysis processes [20][21][22]. …”
Section: Discussionmentioning
confidence: 96%